2004
DOI: 10.1038/sj.ijo.0802740
|View full text |Cite
|
Sign up to set email alerts
|

Physical activity is inversely related to waist circumference in 12-y-old French adolescents

Abstract: BACKGROUND AND OBJECTIVE: Waist circumference (W) has been shown to be a good predictor of cardiovascular risk. The aim of this study was to investigate whether physical activity (PA) is related to W in adolescents as previously shown in adults. DESIGN AND SUBJECTS: Cross-sectional population-based survey of 2714 12-y-old adolescents from the eastern part of France. MEASUREMENTS: Body mass index (BMI) and W were measured. Structured PA, active commuting to and from school and sedentary activities (SED), for ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

10
83
7
7

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(107 citation statements)
references
References 25 publications
10
83
7
7
Order By: Relevance
“…80 In a study of Swiss children, each additional hour of video games played daily was associated with a doubling of obesity risk. 38 Similar significant relationships between sedentary behavior (usually TV) and increased adiposity have been seen cross-sectionally, 41,59,[80][81][82][83][84][85][86][87][88] with some suggestion that the relationship is getting stronger over time. 81 In a study of Australian children, however, after adjusting for covariates, there was no relationship between obesity and time spent with TV, video games, or computers.…”
Section: Physical Inactivity and The Development Of Obesitymentioning
confidence: 85%
See 1 more Smart Citation
“…80 In a study of Swiss children, each additional hour of video games played daily was associated with a doubling of obesity risk. 38 Similar significant relationships between sedentary behavior (usually TV) and increased adiposity have been seen cross-sectionally, 41,59,[80][81][82][83][84][85][86][87][88] with some suggestion that the relationship is getting stronger over time. 81 In a study of Australian children, however, after adjusting for covariates, there was no relationship between obesity and time spent with TV, video games, or computers.…”
Section: Physical Inactivity and The Development Of Obesitymentioning
confidence: 85%
“…56,57 One study found that obese youth are more active than nonobese youth. 58 Two recent cross-sectional studies, however, illustrate the variety of findings: BMI was negatively associated with physical activity in females, but not males, 59 whereas fat mass was negatively associated with physical activity in males, but not females. 60 Cross-sectional studies in this area, however, do not allow determination of cause and effect because physical activity can be both an antecedent and consequence of obesity.…”
Section: Physical Activity and The Development Of Obesitymentioning
confidence: 99%
“…Klein-Platat et al 11 , analyzing if physical activity was related to AC in adolescents, observed that 20.2% of the sample presented overweight and there was no difference in relation to sex.…”
Section: Discussionmentioning
confidence: 99%
“…Convincing information has been reported showing that the practice of physical activity during childhood could be related to a reduced risk of developing overweight and obesity, being an extremely important health element, because it has positive effects beyond well-being, addressing cardiovascular and musculoskeletal health 11 .…”
mentioning
confidence: 99%
“…The most likely explanation is that exercise increases muscle mass and this offsets the effects of fat loss on weight and BMI; an effect also observed in other studies of physical activity. 8,18 We analyzed the results separately by gender because of previous findings of stronger effects either in girls 2,9 or Table 1 Demographic characteristics for pupils completing both years of data collection School PE and adiposity in adolescents J Wardle et al boys. 4,5 Our results resemble the M-Span study, 4 which examined the effects of increased opportunities for activity in school and found reduced adiposity in boys but not girls.…”
Section: Discussionmentioning
confidence: 99%